Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1063/1.1421059
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and transverse structure functions in sheared and unsheared wind-tunnel turbulence

Abstract: The scaling exponents of the longitudinal structure function, 〈Δuxn〉 and two different transverse structure functions: the longitudinal velocity, u, measured in the transverse, y direction (the direction of the mean shear), 〈Δuyn〉, and the transverse velocity v, measured in the flow direction, x, 〈Δvxn〉, up to n=8, are studied in an approximately uniform shear flow [Shen and Warhaft, Phys. Fluids 12, 2976 (2000)], as well as in decaying (shearless) grid turbulence. Results, for low Reynolds numbers (Rλ∼100–200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
82
2
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 24 publications
10
82
2
1
Order By: Relevance
“…Consistency with this prediction was concluded in [8] where it was found that ÿ2:1, while slightly larger were seen in other experiments [9]. Surprisingly, the conclusions of a recent paper [7] are at odds with these findings, and no asymmetry between even and odd transverse exponent was observed.…”
Section: P H Y S I C a L R E V I E W L E T T E R S Week Endingcontrasting
confidence: 46%
“…Consistency with this prediction was concluded in [8] where it was found that ÿ2:1, while slightly larger were seen in other experiments [9]. Surprisingly, the conclusions of a recent paper [7] are at odds with these findings, and no asymmetry between even and odd transverse exponent was observed.…”
Section: P H Y S I C a L R E V I E W L E T T E R S Week Endingcontrasting
confidence: 46%
“…In analogy with the observations made in the stationary case 18,[20][21][22][23][24][25][26] we postulate a scaling behavior…”
Section: ͑6͒mentioning
confidence: 84%
“…The 1941 theory of Kolmogorov [1] is based on the assumption of local isotropy and homogeneity, that is any turbulent flow, independently on the injection mechanism, recovers universal statistical properties, for scales small enough (and far from the boundaries). Indeed, experiments and numerical simulations give strong indications that Eulerian and Lagrangian isotropic/anisotropic small-scales velocity statistics are pretty independent of the large-scale forcing mechanisms [3][4][5][6][7]. Still, we lack a firm understanding for these evidences.…”
mentioning
confidence: 99%